Effect of Dexmedetomidine on Electrocorticography During Epilepsy Surgery under Isoflurane or Propofol Anesthesia: A Prospective, Randomized Trial - Kutum, Chayanika; Khurana, Priyanka; Ganjoo, Pragati; Gupta, Swapan; Singh, Daljit (Asian Journal of Neurosurgery, 2025)
Avoiding or minimizing the interference of anesthetic agents with electrocorticography (ECoG) signals during ECoG-guided epilepsy surgery is vital to the successful resection of the epileptogenic area. Most agents in routine use have widely variable effects like suppression, enhancement, or no impact on the ECoG signals. Dexmedetomidine is reported to have no influence, or minimal depressant effect, on the signals, but studies evaluating its effect on intraoperative ECoG are limited. This study evaluates the effect of dexmedetomidine on ECoG signals during ECoG-guided epilepsy surgeries conducted under either isoflurane-based or propofol-based anesthesia regimens. It also assesses the safety of dexmedetomidine use in these combination forms by determining its impact on hemodynamic parameters, recovery from anesthesia, and incidence of intraoperative awareness.Thirty epilepsy patients, randomized into Group-I (dexmedetomidine-isoflurane, n = 15) and Group-P (dexmedetomidine-propofol, n = 15), underwent ECoG-guided epilepsy surgeries. After dural reflection, dexmedetomidine was administered as a bolus of 1 μg/kg, and ECoG signals were recorded before and after the bolus via brain surface grids. Dexmedetomidine infusion of 0.5 μg/kg/h was thereafter continued throughout surgery in both groups. The effect of dexmedetomidine on ECoG scores, hemodynamic parameters, anesthesia emergence times, and incidence of intraoperative awareness was evaluated in both groups and compared.Dexmedetomidine did not cause ECoG suppression when administered with either propofol or isoflurane anesthesia. However, it caused a significant increase in the ECoG score in Group-I (baseline: 1.8 ± 0.7; post-dexmedetomidine: 2.1 ± 0.9; p = 0.02), while there was no change in scores in Group-P (baseline: 2.0 ± 0.7; post-dexmedetomidine: 2.10 ± 0.7; p = 0.16). The anesthesia emergence time was within defined normal limits in both groups; however, in Group-I, it was significantly longer than that in Group-P (p = 0.03). The hemodynamic parameters were not affected by dexmedetomidine, and there was no incidence of awareness in both groups.Dexmedetomidine, when used with propofol anesthesia, had no effect on the intraoperative ECoG signals, hemodynamic parameters, and anesthesia recovery time. Use of dexmedetomidine with isoflurane anesthesia also did not cause ECoG suppression, but significantly augmented the ECoG scores, while normal hemodynamic and recovery status were maintained. There was no incident of intraoperative awareness in either group. As per this study, the dexmedetomidine-propofol anesthetic regimen appears to be suitable for use in ECoG-guided epilepsy surgeries. However, the ECoG-enhancing effect observed with dexmedetomidine when used with isoflurane necessitates further research for validation and to understand its clinical implications.
Keywords: epilepsy surgery; electrocorticography; dexmedetomidine; isoflurane; propofol; anesthesia